In vivo proteolytic degradation of the Escherichia coli acyltransferase HlyC - Guzman-Verri, Caterina (2001)
Escherichia coli hemolysin (HlyA) is the prototype toxin of a major family of exoproteins produced by Gram-negative bacteria known as “repeats in toxins.” Only fatty acid-acylated HlyA molecules at residues Lys564 and Lys690 are able to damage the target cell membrane. Fatty acylation of pro-HlyA is dependent on the co-synthesized acyltransferase HlyC and the acylated form of acyl-carrier protein. By using a collection of hlyA and hlyC mutant strains, the processing of HlyC was investigated. HlyC was not detected by Western blot in an E. coli strain encoding hlyC and hlyA, but it was present in a strain encoding only hlyC. The hlyC mRNA pattern, however, was similar in both strains indicating that the turnover of HlyC does not occur at the transcriptional level. HlyC was detected in Western blots of cell lysates from an E. coli strain encoding HlyC and a HlyA derivative where both acylation sites were substituted. Similar results were obtained when HlyC was expressed in a hlyA mutant strain lacking part of a putative HlyC binding domain, indicating that this particular HlyA region affects HlyC stability. We did not detect HlyC in cell lysates from hlyC mutants with different abilities to acylate pro-HlyA, suggesting that the degradation of HlyC is not related to the HlyA acylation process. The protease systems ClpAP, ClpXP, and FtsH were found to be responsible for the HlyA-dependent processing of HlyC.